Social Construction of the Cultural Parade in the Month Ramadan in Purwoharjo - Vitto Raditya Pratama; Aeron Fernando Dela Rosa; Novi Fitia Maliha (Journal of Religion, Local Politics, and Law, 2026)
The ogoh-ogoh cultural parade held on the mornings of Ramadan in Purwoharjo District, Banyuwangi Regency, is a fascinating social phenomenon because it involves Hindu religious practices that coincide with the Muslim fasting month. This study aims to analyze the social construction of this cultural parade and the meanings it constructs through interfaith social interactions. This research employed a qualitative approach with phenomenological methods. Data collection involved direct observation and in-depth interviews with Hindu religious leaders, community leaders, and Muslims who participated in or witnessed the cultural parade. The results indicate that the cultural parade is constructed as a symbol of tolerance, togetherness, and respect between religious communities through processes of externalization, objectification, and internalization. The cultural parade serves not only as a religious ritual but also as a medium for strengthening the social identity of the pluralistic and harmonious Purwoharjo community.